TEST performance of a myositis panel in a clinical immunology laboratory in New South Wales, Australia. (1st December 2015) - Tan, Teck Choon; Wienholt, Louise; Adelstein, Stephen
Abstract: Background: There is increasing recognition of a clinico‐serological correlation between the idiopathic inflammatory myopathies and myositis‐specific autoantibodies (MSA). We review the use of a line immunoassay‐based myositis panel incorporating both MSA and myositis‐associated autoantibodies (MAA) in a selected population of patients. Methods: A retrospective analysis of patients with myositis panel assays performed in 2013 were reviewed and compared against clinical diagnoses. Results: A total of 96 patient samples were evaluated, the clinical indications include 60 patients with suspected idiopathic inflammatory myositis (IIM), 24 patients with suspected interstitial lung disease (ILD) and 12 patients with suspected systemic autoimmune disease (SAD). In the myositis group, there were 21 patients diagnosed with IIM and 18 patients diagnosed with IIM had a positive myositis panel. Of the 39 patients without IIM, nine of these patients had a positive myositis panel. In the ILD group, 10 of 24 patients had a positive myositis panel; of these, two were diagnosed anti‐synthetase syndrome (ASS) and five patients with ILD. In the suspected SAD group, three had positive myositis panel and all did not appear associated with their final diagnoses. In patients with a clinical diagnosis of IIM or ILD‐associated SAD, four patients with anti‐PL‐12 were detected, three patients with anti‐signal recognition protein, two patients with anti‐Jo‐1, and two patients with anti‐Mi2. Conclusions: The myositis panel is an objective investigative modality with a sensitivity of 80.00% and a specificity of 75.76% in a setting of high pretest clinical suspicion.